Literature Review: Personal Health Record Untuk Meningkatkan Perawatan Kesehatan Lansia - Riskha Dora Candra Dewi (Bima Nursing Journal, 2020)
Introduction: Personal health record is a patient's personal health record data. The role of personal health records in improving the health of the elderly is still not efficient. Patients are still constrained in accessing and controlling health record data independently. Patients find it difficult to obtain and adopt integrated information about personal health record data that is contained in the health care provider. Another problem is that patients experience limited integration of health records related to security issues such as confidentiality and privacy of health records. Research method: This type of literature study is a literature review. The research objective was to determine the effectiveness of the role of personal health records in improving elderly health care. The search strategy for English studies relevant to the topic was carried out using the ScienceDirect, SagePub, Springer databases limited from 2015 to 2020. The keywords used were “personal health record”, “elderly”, “health care”. Full text articles were reviewed to select studies that matched the criteria. The inclusion criteria in this review were: personal health records, and elderly. A search using the above keywords with the ScienceDirect, SagePub, Springer databases that matched the inclusion criteria was only 13 articles. Research results: The research reviewed in this article uses a variety of methods, namely implementing and evaluating, analyzing and modeling, multi-method descriptive study, mixed-methods study, user-centered design, systematic review, research model and an empirical study, one- way anonymous, mixed design experiment, survey, qualitative interview study, systematic review, study was reviewed and approved. Research using random technique consists of 1 article, while using non-random technique is 12 articles. Conclusion: The role of personal health records can provide information about the health of elderly patients, especially nursing care services based on patient health records. So that this information can be used as a basis for making nursing interventions that are appropriate to the condition of the elderly at that time.